GLOBALISASI DAN TANTANGAN BAGI SISTEM KEUANGAN ISLAM: PERSPEKTIF FILSAFAT EKONOMI ISLAM - Wahyu, Bambang (Al-Infaq: Jurnal Ekonomi Islam, 2011)
The challenge of Islamic financial system today faced on globalization which has numerous power to influence the character and development of Islamic financial system. The risksharing and profit-sharing as core of Islamic finance be improved in order to increase the final solution of modern financial problems. But such ways has discussed mainly related to lack of financial instruments and diversification of portfolio.